2018
DOI: 10.1080/21691401.2018.1470522
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteogenic activity with boron-doped nanohydroxyapatite-loaded poly(butylene adipate-co-terephthalate) fibrous 3D matrix

Abstract: In this study, three dimensional (3D) poly(butylene adipate-co-terephthalate) (PBAT) fibrous scaffolds with more than 90% porosity were fabricated via wet electrospinning method. Amorphous hydroxyapatite (HAp) and boron (B) doped hydroxyapatite (B-HAp) nanoparticles were produced by microwave-assisted biomimetic precipitation and encapsulated into PBAT fibres with the ratio of 5% (w/w) in order to enhance osteogenic activity of the scaffolds. Cell culture studies were carried out with human bone marrow derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…However, a donor organ is required for this purpose; and with respect to bone, autologous grafts (the best option for seeding) are not only limited in supply but also impose donor site problems. Instead, scaffolds are being fabricated from or coated with major components of bone ECM, such as HA or type I collagen, to generate bone-like tissue in vitro 2123 . Furthermore, 3D bioprinting with cell-loaded bioink is emerging as another attractive option 24 , albeit rooted in high-tech devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, a donor organ is required for this purpose; and with respect to bone, autologous grafts (the best option for seeding) are not only limited in supply but also impose donor site problems. Instead, scaffolds are being fabricated from or coated with major components of bone ECM, such as HA or type I collagen, to generate bone-like tissue in vitro 2123 . Furthermore, 3D bioprinting with cell-loaded bioink is emerging as another attractive option 24 , albeit rooted in high-tech devices.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, it has been shown that boron has positive effects on bone healing [ 20 , 25 ]. Boron (B) modulates the osteogenic effects of human bone marrow-derived mesenchymal stem cells [ 70 , 71 ] and mineralized tissue-related proteins as well as the adhesion and proliferation potential of osteoblasts [ 72 ]. In various studies using these elements separately, it has been reported that strontium and boron ions have positive effects on bone formation [ 64 , 65 , 66 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In poly(butylenes adipate-co-terephthalate) (PBAT)/ boron-doped HA composite scaffold, although all scaffolds improved attachment and proliferation, an enhancement in the differentiation of human bone MSCs was observed for scaffolds containing boron-doped HA when compared to scaffolds with pure HA [35]. The study on Saos-2 cell line also showed that the addition of boron-doped HA brought a proliferative effect to the scaffolds consisting of gelatin and bacterial cellulose [27].…”
Section: Effect Of Boron On Biological Properties Of Hamentioning
confidence: 99%
“…No significant reduction in porosity of the scaffold was observed due to boron-doped HA coating. By using a similar synthesis method for boron-doped HA, a scaffold consisting of poly(butylenes adipate-coterephthalate) and 5 wt.% of boron-doped HA was produced [35]. It was detected that boron doping increased fiber diameter by decreasing pore size.…”
Section: Boron-doped Ha As a Scaffoldmentioning
confidence: 99%